Compensatory Recovery after Multisensory Stimulation in Hemianopic Patients: Behavioral and Neurophysiological Components - Grasso, Paolo A.; Làdavas, Elisabetta; Bertini, Caterina (Frontiers in Systems Neuroscience, 2016)
Lateralized post-chiasmatic lesions of the primary visual pathway result in loss of visual perception in the field retinotopically corresponding to the damaged cortical area. However, patients with visual field defects have shown enhanced detection and localization of multisensory audio-visual pairs presented in the blind field. This preserved multisensory integrative ability (i.e., crossmodal blindsight) seems to be subserved by the spared retino-colliculo-dorsal pathway. According to this view, audio-visual integrative mechanisms could be used to increase the functionality of the spared circuit and, as a consequence, might represent an important tool for the rehabilitation of visual field defects. The present study tested this hypothesis, investigating whether exposure to systematic multisensory audio-visual stimulation could induce long-lasting improvements in the visual performance of patients with visual field defects. A group of 10 patients with chronic visual field defects were exposed to audio-visual training for 4 hours daily, over a period of 2 weeks. Behavioral, oculomotor and electroencephalography (EEG) measures were recorded during several visual tasks before and after audio-visual training. After audio-visual training, improvements in visual search abilities, visual detection, self-perceived disability in daily life activities and oculomotor parameters were found, suggesting the implementation of more effective visual exploration strategies. At the electrophysiological level, after training, patients showed a significant reduction of the P3 amplitude in response to stimuli presented in the intact field, reflecting a reduction in attentional resources allocated to the intact field, which might co-occur with a shift of spatial attention towards the blind field. More interestingly, both the behavioral improvements and the electrophysiological changes observed after training were found to be stable at a follow-up session (on average, 8 months after training), suggesting long-term effects of multisensory audio-visual training. These long-lasting effects seem to be subserved by the activation of the spared retino-colliculo-dorsal pathway, which promotes orienting responses towards the blind field, able to both compensate for the visual field loss and concurrently attenuate visual attention towards the intact field. These results add to previous findings the knowledge that audio-visual multisensory stimulation promote long-term plastic changes in hemianopics, resulting in stable and long-lasting ameliorations in behavioural and electrophysiological measures.